Estimate Batam’s Paradiplomacy in Free Trade Area through Content Analysis Regulatory - Putri, Rizqi Apriani (Journal of Islamic World and Politics, 2019)
Batam is one of the areas in Riau Islands. Batam is based on a geographical location directly to Singapore and Malaysia, by passed the international shipping line, from this factor makes Batam as an area for foreign investment for foreign investors. Batam The concept of the Free Trade Zone (FTZ) also focuses on the attraction of foreign investment in the sector of industry exports, income tax, the opening jobs, the absorption the of workforce and the developing local industries. The research used theories of liberalism, effectiveness theory, and paradiplomacy. This article aims to determine the effectiveness of the governance of Free Trade Zone (FTZ) paradiplomacy in Batam area. The method used quantitative used a coding method to detect in the analysis content and qualitative by the author is library research such as books, articles, journals, regulations. The research result is The Indonesian Government's new policy of centralization into decentralization. Give regional authority to manage its own area one of them Batam. Government regulation number 5 year 2011 about free area and free port Batam for Free Trade Zone (FTZ) Batam area. However, some regulations governing FTZ in Batam still occur in inconsistency.